(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2025)
During the early years of World War Two (WWII), the Union of South Africa went through several political, economic and social changes that had profound effects on the creation of what a few years later would be the apartheid system. Racial tensions became stronger as the local political context was in crisis. At the same time, the impact of racial discrimination in WWII introduced further reflections on racial theories, concepts and definitions among South Africans. This paper focuses specifically on debates and disputes about racial definitions among coloured teachers in the Cape. Taking into consideration the historical specificities of that racial definition and racial group in the Union of South Africa, the impact of the international context and the local context, racial adscriptions among coloured teachers changed from exclusivism to non-racialism. Younger teachers went from being proudly coloured to looking for new concepts to redefine a common identity and explicitly choosing the notion of non-Europeans for that. To understand how and why this took place, interviews with former members of the Teacher’s League of South Africa (TLSA), the leading organisation among the coloured educational community, were conducted by the author and placed in dialogue with qualitative research in the Educational Journal and other publications from that teacher’s organisation.